Review of the life history characteristics, ecology and fisheries for deep-water tropical demersal fish in the Indo-Pacific region - Newman, Stephen; Williams, A.; Wakefield, Corey; Nicol, S.; Taylor, B.; O Malley, J. (Springer, 2016)
© 2016, Her majesty the Queen in Right of Australia.Deep-water tropical fishes support locally significant commercial fisheries, high value recreational fisheries, and culturally and economically important artisanal and subsistence fisheries throughout the Indo-Pacific region. The main species captured by these fisheries are deep-water snappers (Lutjanidae), groupers (Epinephelidae), and emperors (Lethrinidae). Quantitative assessments of deep-water tropical fisheries have been limited by a lack of adequate biological and fisheries data. We review the biology and ecology of deep-water tropical fishes, discuss the implications for assessment and management of tropical deep-water fisheries, and provide perspectives on future research priorities. We found that biological and fisheries information is lacking for the majority of deep-water tropical fishes. Furthermore, many studies were constrained by low samples sizes and the use of methods that have not been validated or verified. Most species for which reliable information was available were reported to have extended longevities (>20 years), low rates of natural mortality (M < 0.15), and slow to modest growth rates (K = 0.12–0.25). These life history traits indicate a low production potential for many deep-water tropical fishes, and suggest that sustainable exploitation rates and potential yields may be low. There is a need for more representative and adequate studies of deep-water tropical fishes and for improved fisheries data collection and the use of consistent methods in addition to information sharing to facilitate the development of robust data-poor assessment techniques for these species.